Combining high carotenoid, grain protein content and rust resistance in wheat for food and nutritional security - Padhy, Asish Kumar; Sharma, Achla; Sharma, Himanshu; Srivastava, Puja; Singh, Satinder; Kaur, Parampreet; Kaur, Jaspal; Kaur, Satinder; Chhuneja, Parveen; Bains, Navtej Singh (Frontiers in Genetics, 2023)
Globally, malnutrition has given birth to an alarming predicament, especially in developing countries, and has extensively shifted the consumer preferences from conventional high energy diets to a nutritionally balanced, cost effective, sustainable and healthy lifestyle. With the mandate of developing high-yielding, disease-resistant biofortified staple food (wheat) for catering to the demand-driven market, the current research aimed at stacking together the enhanced grain protein content, carotenoid content, and disease resistance in an elite bread wheat background. Y gene (PsyE1) along with the GpcB1 gene was used as a novel source for enhancing the grain carotenoid and protein content in commercial elite bread wheat cultivar HD2967. The combination also led to combining resistance against all three foliar rusts due to linked genes. A stepwise hybridization using Parent 1 (HD2967+PsyE1/Lr19/Sr25) with Parent 2 (PBW550 +GpcB1/Yr36+ Yr15), coupled with phenotypic-biochemical selection narrowed down 2748 F2 individuals to a subset of 649 F2 plants for molecular screening. Gene-specific markers PsyE1, PsyD1, Xucw108, and Xbarc8 for the genes PsyE1, PsyD1, GpcB1, and Yr15 respectively were employed for forward selection. Four bread wheat lines positive for all the desired genes with high carotenoid (>8ppm) and protein (>13%) content were raised to the F5 generation and will be evaluated for yield potential after bulking. These improved advanced breeding lines developed following multipronged efforts should prove a valuable and unique source for the development of cultivars with improved nutritional quality and rust resistance in the wheat breeding programs.